Comparative studies on physico-mechanical properties of composite materials of low density polyethylene and raw/calcined kaolin - Amit Mallik; Anil K. Barik; Biswajit Pal (Journal of Asian Ceramic Societies, 2015)
The paper describes the preparation of the composite materials of low density polyethylene (LDPE) as the base mixed separately with raw kaolin and the same calcined at 800 °C under the same variation in weight percentage using single-screw extruder and a mixing machine operated at a temperature between 190 and 200 °C. Some of the mechanical and physical properties such as Young's modulus, elongation at break, shore hardness and water absorption were determined at different weight fractions of filler (0, 2, 7, 10 and 15%). It was found that the addition of filler increases the mechanical properties. Absorption test was done in water at different immersion times for different composites. The degree of water absorption of composite materials was found to decrease with increasing wt% of kaolin filler (0–15%) according to Fick's law. Calcined kaolin produces better mechanical properties than raw kaolin.